7, 8-Dihydroxyflavone as a pro-neurotrophic treatment for neurodevelopmental disorders. (October 2015) - Du, X.; Hill, R.A.
Abstract: Neurodevelopmental disorders are a group of conditions that arises from impairments of the central nervous system during its development. The causes of the various disorders are heterogeneous and the symptoms likewise are multifarious. Most of these disorders currently have very little available treatment that is effective in combating the plethora of serious symptoms. Brain-derived neurotrophic factor (BDNF) is a fundamental neurotrophin with vital functions during brain development. Pre-clinical studies have shown that increasing BDNF signalling may be a potent way to prevent, arrest or even reverse abnormal neurodevelopmental events arising from a variety of genetic or environmental causes. However, many difficulties make BDNF problematic to administer in an efficient manner. The recent discovery of a small BDNF-mimetic, the naturally occurring flavonoid 7, 8-dihydroxyflavone (7, 8-DHF), may provide an avenue to allow efficient and safe activation of the BDNF pathway in tackling the symptoms of neurodevelopmental disorders. Here, evidence will be provided to support the potential of 7, 8-DHF as a novel treatment for several neurodevelopmental disorders where the BDNF signalling pathway is implicated in the pathophysiology and where benefits are therefore most likely to be derived from its implementation. Highlights: We discuss the mechanisms and evidence on the neuroprotective effects of the flavonoid 7, 8-dihydroxyflavone (7, 8-DHF). We examine evidence of dysregulation of associated molecular pathways in a range of neurodevelopmental disorders that may benefit from 7, 8-DHF. Studies examining the efficacy of 7, 8-DHF in in vitro and in vivo models with relevance to the neurodevelopmental disorders are discussed. We examine the potential caveats of 7, 8-DHF in the clinical setting.